Business Ties & Investor Power: Activism and Control in the French Context - Ben Mbarek, Noura (Journal of Posthumanism, 2025)
Despite their growing equity stakes, influence, and access to private information, institutional investors in France do not systematically exercise active control over portfolio firms. This study reveals that business ties between institutions and corporations significantly constrain shareholder activism, fostering passivity. Using a sequential mixed-methods approach—19 qualitative interviews with senior executives and a cross-sectional survey of 119 financial institutions, we show that institutions maintaining substantive commercial/operational relationships exhibit markedly lower governance engagement than those with fewer ties. These relationships create conflicts of interest and reputational risks, disincentivizing institutional investors from challenging management. Our findings underscore how business dependencies reshape investor power dynamics and dilute corporate oversight in France’s interconnected financial landscape.